Penguatan Profil Pelajar Pancasila Melalui Penerapan Media Buku Pop-Up - Khasna, Fadzilatul; Zulfahmi, Muhammad Nofan (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2024)
Student Profile Pancasila is an important character value taught to children, especially young children. The Pancasila Student Profile Strengthening Project commonly abbreviated as P5 is part of the program for implementing the Independent Curriculum. One effort to create children who have the character of the Pancasila Student Profile is by introducing local wisdom values and using interactive learning media. This research aims to describe the dimensions contained in Strengthening the Pancasila Student Profile through pop-up book media at Tarbiyatul Athfal Krapyak Kindergarten, Tahunan District, Jepara Regency. The research method used is descriptive qualitative. The subjects in this research were group B4 aged 5-6 years, totaling 21 students in the 2023-2024 school year. The data collection techniques used were observation, interviews and documentation regarding the implementation of children's P5. The data analysis technique used is the Miles and Huberman model which consists of 3 flows, namely data reduction, data presentation, and concluding. The result of this research is the project of Strengthening the Profile of Pancasila Students through the application of pop-up book media containing several emerging dimensions including Global Diversity, Mutual Cooperation, Independence, Critical Reasoning and Creativity. Of these dimensions, the most prominent is the Mutual Cooperation and Creative dimension.